Incidence of Central Diabetes Insipidus among the Patients Undergoing Pituitary Tumor Surgery through Trans-sphenoidal Approach (Bangladesh Medical Journal, 2019)
This study was carried out to find out the incidence of central diabetes insipidus (DI) among the patients undergoing pituitary tumor surgery through trans-sphenoidal approach either endoscopic or microsurgical for the first time. Patients with central (Neurogenic) diabetes insipidus prior to surgery, comorbidities like diabetes mellitus, kidney diseases, electrolyte imbalance, recurrent cases were excluded from this study. Patients were followed up to 7th postoperative day by recording and analyzing findings of postoperative serum electrolytes, urinary specific gravity, hourly urinary volume for establishing diabetes insipidus. 76.9% and 23.1% of patients developed diabetes insipidus those who underwent pituitary tumor surgery by trans-sphenoidal endoscopic approach and microsurgical approach respectively. 70% and 30% of patients did not develop diabetes insipidus those who underwent pituitary tumor surgery by trans-sphenoidal endoscopic and microsurgical approach respectively. There was no significant deference between the approaches were found. Fisher exact test was done and p-value was 0.712. Prediction of DI help us in pre-operative counseling and post-operative management of the patients as well as to reduce complications related morbidity after pituitary tumor surgery.Bangladesh Med J. 2017 May; 46 (2): 10-15